Nostalgia in the time of exile - Petříček, Miroslav (Iluminace, 2000)
A review and analysis of Andrei Tarkovsky's first film made in the West - Nostalgia.
Keywords: film analysis; Nostalgia 1983; Andrei Tarkovsky